Respostas
respondido por:
269
2 - 3X = - 2X + 12 - 3X
- 3X + 2X + 3X = 12 - 2
2X = 10
X = 10 ÷ 2
X = 5
- 3X + 2X + 3X = 12 - 2
2X = 10
X = 10 ÷ 2
X = 5
respondido por:
108
2 - 3X = -2X + 12 - 3X separe os termos, trocando os sinais
-3X + 2X + 3X = 12 - 2 efetue as operações
2X = 10 divida ambos os lados por 2
X = 5
-3X + 2X + 3X = 12 - 2 efetue as operações
2X = 10 divida ambos os lados por 2
X = 5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás